Development of a computer aided decision support tool for selecting organisational improvement initiatives - Ali Hussein, Maher (2014)
The objectives of this research are to: (1) Identify the main factors that should be considered in the selection of organisational improvement initiatives, (2) Develop a computer aided decision support tool (CADST) for selecting organisational improvement initiatives based on Malaysia context, as well as (3) Evaluate and refine the CADST for selecting organisational improvement initiatives . The main factors that should be considered in the selection of improvement initiatives have been identified based on literature review and questionnaire survey. The CADST was developed using Dreamweaver and PHP software. Two research phases were involved which are: (1) Development of CADST for selecting organisational improvement initiatives, and (2) Evaluation and refinement of CADST. Survey was the data collection method used in this research. This survey was conducted through email and face to face interview. Based on the result of the survey, two factors were rated as “Very high importance” (Median 5). The factors are: (1) Ability to gain top management commitment and support to introduce and implement the initiative successfully, and (2) The initiative is aligned to the vision, mission and/or purpose of the organisation. The CADST is evaluated during the survey and refined based on the feedback from the respondents. The refined CADST consists of four elements: (1) Identify possible area for improvement, (2) Select several relevant improvement initiatives, (3) Complete the decision matrix, and (4) Graphical representation of the decision rating. The proposed CADST can be considered as one of the first on-line decision support tool for selecting improvement initiatives based on Malaysia context.